Social Capital, Networks, and Knowledge Transfer - Inkpen, Andrew C.; Tsang, Eric W. K. (Academy of Management Review, 2005)
We examine how social capital dimensions of networks affect the transfer of knowledge between network members. We distinguish among three common network types: intracorporate networks, strategic alliances, and industrial districts. Using a social capital framework, we identify structural, cognitive, and relational dimensions for the three network types. We then link these social capital dimensions to the conditions that facilitate knowledge transfer. In doing so, we propose a set of conditions that promote knowledge transfer for the different network types.